2018
DOI: 10.1093/jas/sky067
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for stayability measures in Nellore–Angus crossbred cows1

Abstract: Beef cow stayability is a complex, economically important trait often used as an indicator of a cow's potential lifetime productivity. Stayability is defined as capability of a cow to maintain a perfect record up to 6 yr of age. This age is commonly cited as a financial break-even point, where initial costs of cow development and maintenance are recovered by her cumulative net income from yearly calf receipts. Later-maturing Bos indicus-Bos taurus crossbred cows may experience reproductive difficulty early in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In general, maternal performance as indicated by calf quality was not considered when cows were annually evaluated for removal in those investigations. Engle et al (2018) reported a genomic region on BTA 5 associated with the probability of avoiding Nelore-Angus crossbred cows remaining in the herd until 6 yr of age, also known as stayability. Components of longevity include reproduction success, udder health and structure (Tolleson et al, 2017), and incisor conditions as aged cows (Riley et al, 2001).…”
Section: Bos Indicus-influenced Breedsmentioning
confidence: 99%
“…In general, maternal performance as indicated by calf quality was not considered when cows were annually evaluated for removal in those investigations. Engle et al (2018) reported a genomic region on BTA 5 associated with the probability of avoiding Nelore-Angus crossbred cows remaining in the herd until 6 yr of age, also known as stayability. Components of longevity include reproduction success, udder health and structure (Tolleson et al, 2017), and incisor conditions as aged cows (Riley et al, 2001).…”
Section: Bos Indicus-influenced Breedsmentioning
confidence: 99%
“…Thus, when using Bos indicus x Bos taurus crossbred cows, we observed higher conception and pregnancy rates compared to Nellore cows. This is probably due to the combined advantages of heterosis and adaptation to the tropical climate of crossbred animals, as reported by studies by (Engle, et al, 2018).…”
Section: Resultsmentioning
confidence: 83%
“…When comparing the Nellore and crossbred animals, we found that the Nellore females had a lower conception rate compared to the other groups (P < 0.05), and the crossbred animals, both without and submitted to the administration of MGA Premix®, showed higher rates of pregnancy (P < 0.05; Table 1). (Engle, et al, 2018). Therefore, understanding the differences between zebu and crossbred females is important for the establishment of correct procedures, regarding the management and evaluation of reproductive parameters, for later adoption of adequate reproductive biotechnologies (Pereira, et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Selection for STAY is difficult because it usually presents low heritability, ranging between 0.08 and 0.14 [ 6 , 7 ], in addition to be a sex-limited trait measured late in female’s life, normally at 76 months of age. All these factors decrease the expected genetic gain when this trait is included as selection criterion.…”
Section: Introductionmentioning
confidence: 99%